Persepsi Mahasiswa Fisip UPR terhadap Penyebaran Hoaks oleh Buzzer melalui Platform TikTok - Mahendra, Made Dwi; Pranata, Meilana Rio; Ramadhany, Ridha; Azizah, Rahmalia Wulan (Resolusi: Jurnal Sosial Politik, 2025)
This study aims to determine the effect of hoaxes spread by political buzzers on the perceptions of students at the Faculty of Social and Political Sciences, University of Palangka Raya (FISIP UPR) through the TikTok platform. The study involved a population of 1,018 students (FISIP UPR) with a sample of 110 respondents selected using random sampling techniques. Data was collected through a Likert scale questionnaire and analyzed using SPSS 27. The results showed that the spread of hoaxes by buzzers had a positive and significant effect on students' perceptions (t count = 7.878 sig. = 0.001 < 0.05), with a contribution of 36.5%. The remaining 63.5% was influenced by other factors such as digital literacy and political orientation. These findings confirm the relevance of framing theory, in which buzzers utilize visual, emotional, and narrative framing to shape the perceptions of young users. This study emphasizes the urgency of improving students' digital literacy in order to strengthen their ability to verify information and reduce their vulnerability to politically-based hoaxes on social media.